Muhammad Husain Tabataba'i dan Tafsir Al-Mizan:: Kajian Syafa’at dalam al-Qur’an Surah al-Baqarah - Khaerurrazikin, Khaerurrazikin; Tahir, Muh. Tarmizi (STAI Darul Kamal NW Kembang Kerang, 2023)
This research is focused on the views and interpretations of Muhammad Husain Thabahaba'i regarding intercession in his commentary, al-Mizan Fi Tafsir al-Qur'an. Discussion of intercession is a debate between Sunni and Shia groups. One of these debates is conveyed in the form of interpretation of the Koran or interpretation of the Koran. Interpretation of verses regarding intercession is influenced by ideological interests, such as Sunni and Shia interests. This means that the Sunni group has a different interpretation from the Shia group regarding intercession, the intercessor, the form of intercession in the Qur'an. This research is a library (Library Research) with the research object focused on Tafsir al-Mizan Fi Tafsir al-Qur'an. This study uses a thematic approach (Maudlu'i), the analytical method used is descriptive-analytical. This study found two major conclusions. First, Tabataba'i understands syafa'at in the sense of obtaining benefits and to keep harm away. As for the group of intercessors, Tabataba'i divides them into two: (a) intercessors in the life of the world and (b) intercessors in the hereafter. Second, in interpreting QS. al-Baqarah: 48, 123, and 254, Tabataba'i understands it as a rejection of giving absolute intercession to the Jews. Meanwhile, in interpreting QS. al-Baqarah: 255. Tabataba'i understands that intercessors are absolutely given by Allah SWT and by groups who get permission or are pleased from Allah, such as the Prophet Muhammad SAW and the Shia Imams.